Sinus node electrogram recording in 59 patients. Comparison with simultaneous estimation of sinoatrial conduction using premature atrial stimulation. - Juillard, A (1983)
Directly measured sinoatrial conduction time was compared with sinoatrial conduction time assessed simultaneously by the single premature atrial stimulus technique in 59 patients: 20 with normal sinus function, 35 with sinus dysfunction, and four with sinus bradycardia but negative indirect methods. In patients with normal sinus function direct sinoatrial conduction time was 102.5 +/- 34 ms (mean +/- 2 SD) and was identical to indirect sinoatrial conduction time. Neither direct sinoatrial conduction time in the basal and return cycle, nor post-return and basal cycle lengths were different. Sinoatrial and atriosinus conduction durations were similar. In sinus dysfunction direct sinoatrial conduction time (average 160 +/- 47 ms) was longer than in normal sinus function. Prolonged direct sinoatrial conduction time may therefore be considered as a criterion of sinus dysfunction. In sinus dysfunction no significant correlation was observed between direct and indirect sinoatrial conduction times. Direct sinoatrial conduction time was equal to (17 patients), longer than (12 patients), or shorter than (six patients) indirect sinoatrial conduction time. These differences can be explained by delayed or incomplete premature depolarisation penetration into the sinus node rather than by the classical pacemaker shift.